Effectiveness of using face masks and personal protective equipment to reducing the spread of COVID-19: A systematic review and meta-analysis of case–control studies - Maryam Hajmohammadi; Amal Saki Malehi; Elham Maraghi (Advanced Biomedical Research, 2023)
Recently published researches show that 59% of all transmission came from asymptomatic transmission and at the time of diagnosis health-care workers (HCWs) tend to present without respiratory symptoms. These evidences have raised questions on whether an essential policy for use of personal protective equipment (PPE) is the best approach in HCW and other people or not. Therefore, this study conducted to investigate the effectiveness of using face masks and PPE in reducing the spread of COVID-19 in health-care and non-health-care settings. This systematic review and meta-analysis study was prepared according to the preferred reporting items for systematic review and meta-analysis statement and guided by meta-analysis of observational studies recommendations. Searches in databases were conducted from December 2019 to July 2021. Random-effects meta-analysis was performed to investigate the effect of using face masks and PPE on spread of COVID-19. Heterogeneity among studies was assessed using Cochran's Q test and the I2 metrics. In total, 9920 individuals from 14 studies were included in this study. In all settings, application of PPE or any type of masks was associated with reduction in risk of COVID-19 (odds ratio [OR] = 0.44; 95% confidence interval [CI]: [0.29, 0.65]; I2 = 85.21%). In the HCW subgroup, the protective effect had a combined OR of 0.33 (95% CI: (0.15,0.73), I2 = 82.61%). Six studies were found protective effects of wearing mask in non-HCWs (OR = 0.58, 95% CI: (0.31, 1.06), I2 = 85.63%). Results suggest that there is association between face mask/PPE use and reduction of COVID-19.